PENERAPAN DESAIN KAOS UNTUK MENUNJANG PARIWISATA DI CV MERCHINDO SERENGAN SURAKARTA - Kurniadi, Edi; Margana, Margana; Supriyadi, Slamet; Kurniawati, Estetika Mutiaranisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Surakarta is one of the cities in Central Java which is known as the city of batik and a tourist destination area which is supported by tourist attractions in the form of various historical sites that have integrated with the culture of the local community. The arrival of tourists to various tourist destinations in Surakarta in addition to enjoying existing tourist objects is also to get souvenirs that have local uniqueness. Apart from hunting batik for souvenirs, many also hunt for distinctive T-shirts, especially for young tourists, because they are inspired like traveling to Bali and Jogja. To provide a new alternative in the form of t-shirts with designs that have local uniqueness, it is planned to partner with CV. Asta Saka Semesta which produces t-shirts, convection, and merchandising. Service methods in the form of training and assistance in making innovative designs for tourist souvenirs; lectures to increase knowledge about survival strategies in business; expansion of marketing through participation in exhibitions; documentation of product samples and procurement of shelves for product documentation that has been produced. The results are 5 innovative designs, namely the design of a tourist attraction patterned t-shirt combined with classic batik motifs, as well as the production process for tourist souvenirs, 2 t-shirt designers have increased their knowledge and skills in making designs to meet the needs of tourists.